PENGEMBANGAN BAHAN AJAR ELEKTRONIK BERBASIS FLIPBOOK MAKER PADA MATERI PROGRAM LINEAR KELAS X SMK - Wulan Noviyanita (Delta: Jurnal Ilmiah Pendidikan Matematika, 2018)
Learning activities at SMK Muhammadiyah Kesesi are still less use of instructional media, teachers still use the available package books in school and power point at the time of learning so that students feel bored. This research develops electronic teaching materials based on flipbook maker linear class X material program at SMK Muhammadiyah Kesesi. The purpose of this research is to know the validity and the practicability of the developed electronic materials. The research conducted using the Borg & Gall development model included in Putra (2012:120-121). The steps of the research are: 1) research and data collection; 2) development of initial product type / shape; 3) initial field trials; 4) field implementation test; 5) product improvement. There are 8 validator in this research and there are 28 students as respondent. Based on the research results obtained the average total criteria from the validator V a  4, 1. According to the validation criteria, it can be conclud that the electronic teaching materials using kvisoft flipbook maker application on the material linear, class X SMK is said to be valid. While the calculation of the value of the practicality of electronic materials using kvisoft flipbook maker application on material linear class X SMK obtained from the student response questionnaire is 85,9 %. It means, the developed electronic teaching material is declared to be practical. Therefore, it can be concluded that the electronic teaching materials using kvisoft flipbook maker application on material linear class X SMK is suitable to use as one of the learning resources.